Targeting the pentose phosphate pathway increases reactive oxygen species and induces apoptosis in thyroid cancer cells. (1st January 2020) - Liu, Chien-Liang; Hsu, Yi-Chiung; Lee, Jie-Jen; Chen, Ming-Jen; Lin, Chi-Hsin; Huang, Shih-Yuan; Cheng, Shih-Ping
Abstract: The pentose phosphate pathway (PPP) plays an important role in the biosynthesis of ribonucleotide precursor and NADPH. Cancer cells frequently increase the flux of glucose into the PPP to support the anabolic demands and regulate oxidative stress. Consistently, metabolomic analyses indicate an upregulation of the PPP in thyroid cancer. In the present study, we found that the combination of glucose-6-phosphate dehydrogenase (G6PD) and transketolase inhibitors (6-aminonicotinamide and oxythiamine) exerted an additive or synergistic effect on cell growth inhibition in thyroid cancer cells. Targeting PPP significantly increased cellular reactive oxygen species (ROS) and induced endoplasmic reticulum (ER) stress and apoptosis. Suppressed cell viability could be partially rescued with treatment with the ROS scavenger or apoptosis inhibitor but not ER-stress inhibitor. Taken together, dual PPP blockade leads to pharmacologic additivity or synergism and causes ROS-mediated apoptosis in thyroid cancer cells. Highlights: Metabolomic analyses suggest an upregulation of the pentose phosphate pathway (PPP). Dual inhibition of both branches results in pharmacologic additivity or synergism. PPP blockade causes ROS-mediated apoptosis in thyroid cancer cells.